Collective impact facilitators: how contextual and procedural factors influence collaboration*. Issue 2 (14th March 2016) - Gillam, Rebecca J.; Counts, Jacqueline M.; Garstka, Teri A.
Abstract: Collective impact (CI) has primarily been applied to solving organic adaptive problems that evolve over time. While this framework aligns broadly with the collaboration literature, the dynamic, and at times forced, nature of this work in practice poses challenges. This study used a quasi-experimental design to test a CI model of the facilitators of mandated collaboration measured by the Levels of Collaboration Scale and the Wilder Collaboration Factors Inventory. Hierarchical linear regression techniques and data from 126 early childhood community stakeholders were used to test the impact of facilitators, including key elements of CI, on perceived collaboration. Findings show that: (1) policy mandates have a significant, positive correlation with collaboration; and (2) the only significant predictor of collaboration is informal relationships. This analysis suggests a hybrid process, combining key elements of CI with a focus on relationship building, to support effective collaboration practice.